Controllable synthesis of carbon encapsulated iron phosphide nanoparticles for the chemoselective hydrogenation of aromatic nitroarenes to anilines. Issue 5 (19th March 2018) - Zhu, Yanan; Yang, Shuliang; Cao, Changyan; Song, Weiguo; Wan, Li-Jun
Abstract : Iron phosphide nanoparticles encapsulated in a doped carbon matrix showed high activity and good selectivity in the hydrogenation of aromatic nitroarenes to anilines. Abstract : Selective hydrogenation of nitroarenes is an important chemical transformation to obtain functionalized anilines as key intermediates for pharmaceuticals and fine chemicals. Compared to the well-studied noble metal catalysts, heterogeneous catalysts based on low-cost transition metals are rarely reported. In this study, we developed an efficient and controllable route to synthesize a new kind of heterogeneous catalyst of iron phosphide nanoparticles encapsulated in a doped carbon matrix for the chemoselective hydrogenation of aromatic nitroarenes to anilines. Making use of the chemical reaction between Fe atoms in a MIL-88B-NH2 core and phosphorus atoms in a poly(cyclotriphosphazene-co-4, 4′-sulfonyldiphenol) (PZS) shell, iron phosphide nanoparticles encapsulated in a doped carbon matrix were successfully prepared through direct calcinations of a Fe-MOF@PZS core@shell precursor at 900 °C for 2 h under an Ar atmosphere. Due to the relative high surface area and porous structure as well as small nanoparticles, the prepared catalyst showed high catalytic activity, excellent selectivity and recyclability for the hydrogenation of aromatic nitroarenes to anilines.